Total prohibition of smoking but not partial restriction effectively reduced exposure to tobacco smoke among restaurant workers in Finland - Jere Reijula; Tom Johnsson; Simo Kaleva; Tapani Tuomi; Kari Reijula (International Journal of Occupational Medicine and Environmental Health, 2013)
Objectives: To assess work-related exposure to tobacco smoke in Finnish restaurants, a series of nationwide questionnaire surveys were conducted among restaurant workers and the levels of indoor air nicotine concentrations were measured in restaurants. The survey aimed to evaluate the impact of the smoke-free legislation in general and in particular after the total smoking ban launched in 2007. Materials and Methods: In 2003-2010, four national questionnaire surveys were conducted among restaurant workers and the concentration of nicotine in indoor air was measured in different types of restaurants, bars and nightclubs. Results: Between 2003 and 2010, the proportion of restaurant workers reporting occupational exposure to tobacco smoke dropped from 59% to 11%. Among pub workers, the decrease was from 97% to 18% and in workers of dining restaurants from 49% to 10%, respectively. The median concentration of nicotine in indoor air of all restaurants decreased from 11.7 μg/m³ to 0.1 μg/m³. The most significant decrease was detected in pubs where the decrease was from 16.1 μg/m³ to 0.1 μg/m³. Among all restaurant workers, in 2003-2010 the prevalence of daily smokers was reduced from 39% to 31% in men and from 35% to 25% in women. Conclusion: Total prohibition of smoking but not partial restriction in restaurants was effective in reducing work-related exposure to tobacco smoke. Strict tobacco legislation may partly be associated with the significant decrease of daily smoking prevalence among restaurant workers.